Kontrowersje wokół długoterminowych badań Gillesa-Erica Séraliniego nad bezpieczeństwem zdrowotnym kukurydzy GMO - Katarzyna Lisowska; Alexander Cortez (Studia Ecologiae et Bioethicae)
At the end of the year 2012, Food and Chemical Toxicology published a long-term study by Seralini et al., describing the safety evaluation of genetically modified NK603 maize and Roundup herbicide. Contrary to previous, short-term studies, this experiment revealed some negative effects of these substances on the health of experimental animals. GM feeds and Roundup generate revenue worth millions of dollars. This may be the reason why Seralini’s paper has became the subject of much heated criticism, mainly from parties linked to business and agro-biotechnology. After one year of debate, the editors of Food Chem Toxicol. decided to retract the paper, an unprecedented event given that the published article was peer-reviewed and there was no evidence of plagiarism or fraud. Here, we stress the results of Seralini’s study, discuss the methodological hints of that work and cite the commentaries on the whole situation.